2018 3rd International Conference of the Portuguese Society for Engineering Education (CISPEE) 2018
DOI: 10.1109/cispee.2018.8593409
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in first-year students’ expectations towards a new engineering multidisciplinary curriculum

Abstract: Research on engineering first-year students' expectations and perceptions is important to understand what influences interest, achievement and persistence. This is particularly relevant when assessing the impact of new engineering education curricula. This paper reports a quantitative analysis of a pre-degree survey targeting students' expectations at the very beginning of the new Integrated Engineering Programme, which spans across the whole UCL Faculty of Engineering Sciences. Of a cohort of approximately 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We included learning activities which highlighted engineering innovation and creativity [7] such as those focussed on robots in space and sound and music in virtual reality. We also chose to emphasise not just the technical underpinning of engineering, but also important social and human-centred aspects, for example in the learning steps concerning healthcare and water hygiene [6,8,10,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We included learning activities which highlighted engineering innovation and creativity [7] such as those focussed on robots in space and sound and music in virtual reality. We also chose to emphasise not just the technical underpinning of engineering, but also important social and human-centred aspects, for example in the learning steps concerning healthcare and water hygiene [6,8,10,25].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and engineering educators have posited a variety of reasons for this apparent lack of diversity in engineering which include [6][7][8][9][10]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several studies found that men self-reported an overall higher level of softs skills, when compared to women (Alpay & Walsh, 2008; Whittle & Eaton, 2001). However, women seem to consider these skills as more important (Direito et al., 2018; Nabi & Bagley, 1998), and tend to work harder to acquire them (De Juan-Vigaray et al., 2012), in comparison to men. Other studies have found that men and women endorse different dimensions of self-efficacy leadership (Javidan et al., 2016), and that women score higher on specific personal skills such as team working, time management, planning/ organizing, and prioritizing skills (Nabi & Bagley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These constraints from the learning environment could become obstacles for women engineering students to develop a sense of belonging in engineering groups (Godwin & Potvin, 2017;Hatmaker, 2013). Moreover, researchers pointed out that he chill clima e also had a negative influence on internal sources for engineering identity, including higher pressure to pursue engineering, lower competence beliefs, fewer intrinsic motivations, and less selfrecognition as future engineers (Baker et al, 2007;Direito et al, 2018;Pierrakos et al, 2009).…”
Section: Impact Factors Of Engineering Identity Developmentmentioning
confidence: 99%